2003
DOI: 10.1080/713836148
|View full text |Cite
|
Sign up to set email alerts
|

Shape Optimization of Cutoff in a Multiblade Fan/Scroll System Using Response Surface Methodology

Abstract: This article presents a new method that overcomes three-dimensional effects by using twodimensional computational fluid dynamics (CFD) and response surface methodology (RSM). The method is applied to shape optimization of cutoff. The distributions of velocity and pressure obtained by two-dimensional CFD analysis are compared with those of threedimensional CFD analysis and experimental results. RSM with central composite designs is used to obtain an approximated volume flow rate in terms of the angle and curvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Then, the response surface method with three-dimensional Navier-Stokes analysis had been applied well for the design of blade section of axial compressor rotor [7], low speed axial fans [8] and forward-curved blades centrifugal fans [9] respectively. Han S. Y. and Maeng J. S. [10] had studied the characteristics of the inactive zone, and optimized the shape of cutoff by using a two-dimensional RANS analysis and response surface method. Samad et al [11] had reported on the blade modification to optimize a centrifugal compressor using multiple surrogate models.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the response surface method with three-dimensional Navier-Stokes analysis had been applied well for the design of blade section of axial compressor rotor [7], low speed axial fans [8] and forward-curved blades centrifugal fans [9] respectively. Han S. Y. and Maeng J. S. [10] had studied the characteristics of the inactive zone, and optimized the shape of cutoff by using a two-dimensional RANS analysis and response surface method. Samad et al [11] had reported on the blade modification to optimize a centrifugal compressor using multiple surrogate models.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical CFD analysis enables 3D simulation of the flow inside the air purifier, including estimation of flow speed and noise distribution [1][2][3][4]. Additionally, there have been many studies [5][6][7][8] that used design of experiments (DOE), which maximizes the information gained through minimal testing by appropriately posting test points, as well as design optimization (DO), which aims to obtain an optimum solution by combining and approximating the estimated noise in each test point.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [10][11][12] applied well the response surface method and three-dimensional Navier-Stokes analysis to design blade section of axial compressor rotor, low speed axial fans, etc. Han and Maeng [13] studied the characteristics of the inactive zone, and optimized the shape of cut-off by using a two-dimensional RANS analysis and response surface method. Recently, artificial neural networks (ANN) and genetic algorithms (GA) have been employed for the optimization design of low pressure axial flow fans [14,15] and turbine blades [16,17] gradually.…”
Section: Introductionmentioning
confidence: 99%